ECOLOGICAL AND SOCIO-ECONOMIC IMPLICATION OF CLIMATE CHANGE AND VARIABILITY ON TOURISM IN KILIMANJARO MOUNTAIN NATIONAL PARK, TANZANIA - Minja, Gileard S. (European Scientific Journal, ESJ, 2015)
The study assessed social-economic and ecological implications of climate change and variability on tourism in Kilimanjaro National Park and adjacent communities. Specifically the study analyzed ecological and socioeconomic implications of climate change and variability in Kilimanjaro National Park. Further, the study identified climate change and variability adaptation strategies in the area. Also the study examines policy implication of climate change and variability on tourism. Both purposeful and random sampling was used for villages and households selection in the area. Primary and secondary data both qualitative and quantitative were used in this study. Primary data were mainly collected using structured household questionnaire. PRA methods such as questionnaire, Focus Group Discussions (FGD), key informant, time line, drivers of change and direct field observation were used to obtain data for CC&V implication on social economic and ecological in the area. Findings revealed that climate change and variability affects socio-economic and ecological resources in diverse ways. In terms of economic implications responses to Yes were significance X2 0.05=7.81, Df = 3. The presented calculated chi-square X2 = 9.214 was larger than tabulated; therefore there was a significant statistical difference in socio-economic implications. Education, capacity building, soft loans, grants were adaptation strategies adopted. It is anticipated that the information obtained from this study will be beneficial to researchers, policy makers and conservation officers in National Parks in Tanzania to mainstream effective mitigation, coping and adaptation strategies for sustainable tourism and ecosystem management.